Meningkatkan Kemampuan Membaca Intensif Dengan Metode Cooperative Integrated Reading Composition Pada Peserta Didik: Improving Teachers' Professional Competence To Develop 2013 Curriculum Teaching Materials Through Workshop At Samba Danum SDN-2 - Sumarsih (Neraca: Jurnal Pendidikan Ekonomi, 2023)
The objectives of the School Action Research with the title: "Improving Teacher Professional Competence to Develop 2013 Curriculum Teaching Materials Through Workshops at SDN-2 Samba Danum" are as follows: 1) Describe the Techniques and Steps for Implementing the Workshop to Improve Teacher Professional Competence to Create 2013 Curriculum Teaching Materials at SDN-2 Samba Danum.; 2) Proves that the implementation of the workshop can improve the professional competence of teachers to develop teaching materials for the 2013 curriculum at SDN-2 Samba Danum. The results of the study are the assessment of the teacher's work in compiling teaching materials for the 2013 curriculum at SDN-2 Samba Danum, it can be concluded that out of 12 teachers who took part in the workshop activities for compiling teaching materials for the 2013 curriculum, it was proven that 12 teachers received grades with criteria A (Very Good). ), there were 9 teachers or 75% who scored with criteria B (Good), there were 3 teachers or 25% who scored with criteria C (Good enough), there were 0 teachers or 0% who got scores with criteria D (Poor), and there were 0 teachers or 0% who scored with criterion C (Very Poor).